Effect of fruiting-related genes on the formation of volatile organic compounds in the mushroom Schizophyllum commune - Orban, Axel; Schwab, Lisa Janaina; Lugones, Luis G.; Wösten, Han A. B.; Rühl, Martin; Justus Liebig University Giessen (My University, 2023)
In fungi, little is known about connections between volatile organic compound (VOC) formation and developmental stages that are amongst others triggered by fruiting-related genes (FRGs). We analysed the volatilomes of Schizophyllum commune during different developmental stages in a variety of FRG-deletion strains and wild-type strains. The deletion strains Δtea1Δtea1, Δwc-2Δwc-2 and Δhom2Δhom2 were unable to develop fruiting bodies, and Δfst4Δfst4 formed only rudimentary fruiting body structures. Early developmental stages of these strains were dominated by esters, including methyl 2-methylbutanoate, ethyl 2-methylbutanoate, isobutyl 2-methylpropionate, and 2-methylbutyl acetate, of which the last three were not found in the headspace (HS) of the wild-type samples. Compared to the wild type, in the HS of hom2con samples, that are able to form fruiting bodies, methyl 2-methylbutanoate was the most abundant substance at early stages (68–81% of the total peak area). In contrast to fruiting body forming strains, Δtea1Δtea1, Δwc-2Δwc-2, Δhom2Δhom2 and Δfst4Δfst4 showed less sesquiterpenes in the HS. However, the sesquiterpenes found in the HS of FRG-deletion strains, namely, (E)-nerolidol, δ-cadinene, L-calamenene, α-bisabolol and β-bisabolene, were not present in hom2con or wild-type strains that mainly formed fruiting bodies and barely mycelium. Several sesquiterpenes, including α-guaiene, chamigrene and γ-gurjunene, were only found in presence of fruiting bodies. Our results show remarkable connections between FRGs, fruiting body development and VOC production in S. commune, especially counting for sesquiterpenes. Future studies are needed to reveal whether FRGs directly regulates VOC formation or indirectly by changing the phenotype.
Keywords: ddc:540